Children's literature of the Harlem Renaissance - Capshaw, Katharine (Blacks in the diaspora., 2004)
The Harlem Renaissance, the period associated with the flowering of the arts in Harlem, inaugurated a tradition of African American children's literature, for the movement's central writers made youth both their subject and audience. W.E.B. Du Bois, Carter G. Woodson, Langston Hughes, Alice Dunbar-Nelson, and other Harlem Renaissance figures took an impassioned interest in the literary models offered to children, believing that the "New Negro" would ultimately arise from black youth. As a result, African